In vivo inhibitory effect of Panicum maximum root extract on alpha amylase and alpha glucosidase enzymes of rats - Nwakaego, Ebong (Journal of Current Biomedical Research, 2023)
Panicum maximum Jacq, (Poaceae) a medicinal plant used traditionally in the treatment of diseases including diabetes was evaluated for effect on alpha amylase and alpha glucosidase enzymes in vivo. The leaf extract (137, 273, and 547 mg/kg) of Panicum maximum were investigated in vivo for inhibitory effect on alpha amylase and alpha glucosidase enzymes using starch, sucrose and maltose as substrates. Acarbose was used as reference drug. The leaf extract non dose-dependently caused significant (p<0.05) reduction in blood glucose levels of treated rats with the various substrates used. The results suggest that the leaf extract of Panicum maximum have the potentials to inhibit alpha amylase and glucosidase in rats.